Signos da política, representações da subversão: a divisão de censura de diversões públicas na ditadura militar brasileira - Ana Marilia Menezes Carneiro (2013)
The censorship was one of the most important and emblematic instruments of the military government in Brazil. While the press censorship acted without legal support, the censorship of public entertainment (radio, music, film, theater, television and even circus) was protected by a legal status, even in some democracies. Nevertheless, during the Brazilian dictatorship, it assumes specific features, according with political demands. This text analyses in which way political practices and representations were mobilized by the Division of Censorship of Public Entertainment during this period. To this effort, it focuses specially in the anticommunist representations, explaining the ways in which censorship affected political interventions, although the main concern of the DCDP was with moral issues. Investigating the prohibition production codes (and not the forbidden artistic works) and getting closer to the reception and diffusion of conservative values in certain sectors of the population (by the analysis of letters sent to the censorship department), it is intended to discuss especially political and ideological concepts that permeated the work of the censorship service. Throughout the text, it try to contrast the faint lines that separate the moral and political dimensions, showing how these scopes were connected to the anticommunist discourse mobilized by the censors and especially by the military information department.